From Zero Collaboration to Teamwork: Forms of Teacher Collaboration and Factors That Support or Hinder It - Katrin Saks; Pihel Hunt; Äli Leijen; Liina Lepp (Education Sciences)
Teachers tend to prefer an individualistic approach to their teaching process and collaborate with colleagues only on certain occasions. This research explored the forms of collaboration and supporting and hindering factors proceeding from the frameworks of the teacher–teacher interaction continuum and team entitativity. The findings indicated more active collaboration at lower levels of the continuum—storytelling and scanning ideas, aid and assistance, and sharing. The interviews with teachers pointed to personal relationships and the will to act together as the main triggers of collaboration. The role of the administration when supporting and hindering collaboration appeared in higher levels of the interaction continuum. The study contributes to the continuum by proposing an additional unit—zero collaboration, which is a completely individualistic activity with no purposeful collaboration with colleagues.